2012
DOI: 10.1113/jphysiol.2011.224352
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for the in vivo assessment of cardio‐renal function in zebrafish (Danio rerio) larvae

Abstract: Key points• The anatomical structures and discrete nephric regions of the pronephric zebrafish kidney are similar to those of the mammalian nephron.• Renal blood supply and subsequent renal filtration rate are both key determinants of kidney function.• Our study developed classical functional assays for larval zebrafish that effectively model the effects of the nephrotoxin gentamicin and high salt loading.• The techniques demonstrate the disruption in ion and water balance resulting from reduced cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 11 publications
2
43
0
Order By: Relevance
“…Further, whole-mount immunofluorescence demonstrated that gentamicin injected fish had a disruption of cell polarity, evidenced by diffusion of anti-Na + /K + ATPase α-subunit (α6F) in the cytoplasm, which is typically concentrated in the basolateral membrane of proximal tubular cells. Taken together, these data demonstrated the many similarities between gentamicin-induced pronephric injury in zebrafish and mammalian AKI, consistent with prior observations [3234]. …”
Section: Insights Into Aki From Chemical Geneticssupporting
confidence: 91%
“…Further, whole-mount immunofluorescence demonstrated that gentamicin injected fish had a disruption of cell polarity, evidenced by diffusion of anti-Na + /K + ATPase α-subunit (α6F) in the cytoplasm, which is typically concentrated in the basolateral membrane of proximal tubular cells. Taken together, these data demonstrated the many similarities between gentamicin-induced pronephric injury in zebrafish and mammalian AKI, consistent with prior observations [3234]. …”
Section: Insights Into Aki From Chemical Geneticssupporting
confidence: 91%
“…Salinity solutions were prepared as previously described (24,60). Captopril (C4042, Sigma-Aldrich) was administered at 0.1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…It is no surprise that since zebrafish are an excellent animal model they have also been utilized in studying the kidney [23][24][25] . To date, zebrafish have been used to advance our knowledge of renal development as well as aspects of several kidney disease phenotypes [26][27][28][29][30][31][32] . In particular, mutagenesis screens in zebrafish have been used to identify genes that cause kidney malformations, which led to the discovery of ciliogenesis genes that cause renal cyst formation when disrupted [33][34][35][36][37][38] .…”
Section: The Zebrafish: a Model For Kidney Researchmentioning
confidence: 99%